Snake Envenomation: A Rare Cause of Hypopituitarism - A Case Report - Lachhwani, Harshita (International Journal of Medical Students, 2025)
BACKGROUND: Snake bites are frequent in a developing country like India, especially rural areas. Mostly they are minor and never reported but sometimes they may be serious and fatal. Occasionally, Viper bites induced hemorrhagic complications land the patient into hypovolemic shock, leading to Sheehan’s syndrome-like condition and causing panhypopituitarism. The onset of features of panhypopituitarism may be delayed by a few years. THE CASE: With this background, we are presenting a case of a 27-year-old male who presented to us in April 2022 with a history of reduced growth of facial hair, which was normal a few years back, along with associated symptoms of polyuria, polydipsia, polyphagia, and cold intolerance. Most importantly, he gave a history of a viper bite in 2017 for which he was hospitalized in a state of hypovolemic shock. At the time of presentation to us, his BP was 96/64 mm Hg, and pulse was 70/min. His investigations showed low T3, T4, TSH, low testosterone, reduced levels of Sr FSH, Sr LH, and Sr Prolactin. His 24-hour urine volume was 2.8 L, his testicular volume was low, and MRI Brain showed empty Sella. He was managed conservatively with oral hydrocortisone, levothyroxine tablets, and injectable testosterone. He has been under our follow-up for the last 2 years and has responded well to the treatment both symptomatically and in terms of blood parameters. CONCLUSION: Hypopituitarism is a rare complication of snake bite. Therefore, it is important to undergo relevant hormonal tests in persons who have a history of snake bite in the past.